DEVELOPMENT OF INTERACTIVE E-MODULE OF JIGSAW MODEL ON SOLAR SYSTEM MATERIAL INTEGRATED WITH NGADA LOCAL WISDOM IN JUNIOR HIGH SCHOOL - Pajo, Bernadethe Ines Sede; Dinatha, Ngurah Mahendra; Dolo, Fransiskus Xaverius; Suparmi, Ni Wayan (Jurnal Ilmiah Pendidikan Citra Bakti, 2026)
This study aimed to develop an interactive e-module based on the Jigsaw model integrated with Ngada local wisdom on the topic of the solar system and to examine its validity and practicality. The study employed a Research and Development method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation. The research subjects involved material experts, media experts, language experts, science teachers, and seventh-grade students. Data were collected through observation, interviews, validation sheets, and user response questionnaires, and then analyzed using descriptive quantitative techniques. The results showed that the e-module obtained an average validity score of 3.96, which falls into the very valid category. The practicality test showed percentages of 95.83% from teachers and 98.13% from students, both categorized as very practical. The product also presents the material systematically, supported by illustrations, videos, easy navigation, and Jigsaw learning steps that encourage discussion, responsibility, and active student participation. Thus, the Jigsaw-based interactive e-module integrated with Ngada local wisdom is considered feasible for use in science learning on the solar system, as it supports more active, collaborative, contextual, and student-centered learning and has the potential to improve students’ interest in learning and their conceptual understanding of solar system phenomena in a meaningful way.